Effect of deficiencies and excesses of phosphorus, potassium and boron on the physiology and growth of avocado (Persea americana, cv. Hass) plants - Novoa, María Alejandra; Miranda, Diego; Melgarejo, Luz Marina (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
In order to observe the effects of nutrients: potassium (K), boron (B) and phosphorus (P), on physiological and growth variables in avocado var. Hass, seven treatments and four repetitions with three dose levels were evaluated: (1) deficiency of the respective element: 50% or half of the complete fertilization, (2) complete or control treatment: 100%, and (3) excess of the respective element, 150% above the complete fertilization, arranged in a completely random design. The plants were grown in polyethylene bags with soil and cultivated under greenhouse conditions; weekly fertilization and irrigation were also carried out. The evaluated variables included leaf area (LA), number of leaves (NL), relative chlorophyll content (CC), maximum photochemical efficiency of PSII (Fv/Fm) and transpiration (E); the symptomatology of deficiencies and excesses were described in the leaves. The LA, NL and CC values were lower in relation to the control. Similarly, the Fv/Fm and E were lower compared to the control, suggesting probable stress caused by the treatments, presenting a greater proportion of P, followed by K and B. The visual signs of nutrient stress were observed more clearly in the plants subjected to deficiency than in those subjected to excess, consistent with what has been reported for this variety.